The Effect of Ageing Population on House Prices in Malaysia. An Autoregressive Distributed Lag (ARDL) Cointegration Approach - Anthony Mariadas, Paul; Abdullahb, Hussin; Abdullahc, Norehan (International Journal of Psychosocial Rehabilitation, 2020)
The past decade has witnessed a notable increase in housing prices across countries, which raises concern about its impact on social and economic aspects. Although property investment plays an essential role in supporting the growth of economics through its influence on the aggregate demand level, a continuous increase in housing prices may bring serious economic consequences. Hence, understanding the potential factors that contribute towards the significant increase in housing prices is useful for policy implications. The main objective of this study is to investigate the effects of an aging population on housing prices in Malaysia. By utilizing the annual time series data from 1988 to 2017, the empirical analysis, which is conducted using the autoregressive distributed lag (ARDL) modelling approach, reveals that in the long run, all the variables are found to be statistically significant with house prices, whereby gross domestic product, inflation, stock market, and ageing population are positively associated with house prices, while the rest of the variables are positively related. These findings provide some guidelines for a policy formulation to moderate the increase in housing prices in order to maintain the economic stability of the country and indirectly help the government in realizing its vision of becoming a high-income country.